Desain dan Fungsionalitas Temporary Office Penggunaan Bangunan Prefabrikasi KSOP Kelas 2 Patimban: Tinjauan Arsitektural dan Material - Edelweis; Mohamad Isro Arroekhan (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Patimban Port is a national strategic project supported by various infrastructures, one of which is the Temporary Office of KSOP Class 2 Patimban, built using a modular prefabricated construction system. This study aims to analyze the architectural design and building materials, as well as assess its functionality in supporting port operations. Through a qualitative method with descriptive analysis, this research reveals that the use of materials such as sandwich panels and lightweight steel provides efficiency in terms of durability and thermal insulation, although challenges related to acoustic insulation remain. The applied ventilation and lighting systems support user comfort but can still be improved. Overall, this Temporary Office significantly contributes to operational efficiency at the port with an estimated service life of 10-15 years, although improvements in areas such as sound insulation and the development of permanent facilities are needed.